1998
DOI: 10.1093/humrep/13.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of MicroSort flow cytometry for producing sperm populations enriched In X- or Y-chromosome haplotypes: a blind trial assessed by double and triple colour fluorescent in-situ hybridization

Abstract: Using fluorescent in-situ hybridization (FISH) we have evaluated, on a blind basis, the efficiency of flow cytometry to separate human X- and Y-chromosome bearing spermatozoa. Our data demonstrate that human spermatozoa can be sorted to a purity of 80-90% for X spermatozoa and of 60-70% for Y spermatozoa. Our results using triple FISH fully agree with the sorting treatment used in each case and corroborate the efficiency of the flow sorting technique for sperm sex selection. In these limited samples (200-500 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…The use of DNA probes in conjunction with fluorescent in situ hybridization (FISH) has shown that flow cytometric sorting is 82% accurate for sorting the X-sperm and 75% accurate for the Y-sperm [19]. More recently, however, the flow cytometric sorting method was reported to have 87% and 67% accuracy rates in sorting for X-and Y-sperm, respectively [20].…”
Section: Discussionmentioning
confidence: 99%
“…The use of DNA probes in conjunction with fluorescent in situ hybridization (FISH) has shown that flow cytometric sorting is 82% accurate for sorting the X-sperm and 75% accurate for the Y-sperm [19]. More recently, however, the flow cytometric sorting method was reported to have 87% and 67% accuracy rates in sorting for X-and Y-sperm, respectively [20].…”
Section: Discussionmentioning
confidence: 99%
“…The two methods currently commercially available are sperm separation and preimplantation genetic diagnosis (PGD) [1][2][3][4][5][6]. Even though the intended use of such technologies was to prevent the birth of children with sexlinked genetic disorders, these technologies are being increasingly used for preimplantation sex selection for nonmedical reasons (http://www.microsort.net/index.php, accessed March 1, 2007) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The technology employs a flow cytometer that separates the 2.8% heavier X-from Y-bearing sperm to produce an X-or Y-enriched sperm sample for artificial insemination or in vitro fertilization (2)(3)(4). Upon successful completion of the clinical trial (which began in 1995), the potential exists for widespread dissemination and marketing of this technology throughout the United States (5).…”
mentioning
confidence: 99%